Numerical Simulation of Chip Formation in Metal Cutting Process - Zhao Yongjuan; Pan Yutian Pan Yutian; Huang Meixia (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2012)
In order to study the chip formation mechanism in metal cutting process, based on finite element software ABAQUS, the paper established finite element model and carried out numerical simulation on serrated chip formation of Ni-base superalloy GH4169 and ribbon chip formation of 45# steel respectively. In addition, this paper also analyzed the influence law of three factors (cutting speed, feed rate, back cutting depth) on cutting force and the distribution rule of cutting heat in serrated chip formation of GH4169.